2011
DOI: 10.1111/j.1464-410x.2010.09953.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate and the Risk of Urolithiasis

Abstract: other methods employed showed a far greater Δ X 2 : in four groups ( ≤ 10%, > 10-25%, > 25-75%, > 75%) the added prognostic value had a Δ X 2 of 15.0 ( P = 0.0001) while, interestingly, the added value was nearly as high for the simpler 10% cut-off variable ( Δ X 2 = 13.0, P = 0.0004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Our study findings highlight an important association between topiramate usage and stone development and confirm the results of several previous studies. Topiramate has previously been associated with an increased risk for nephrolithiasis in patients with refractory epilepsy, both as an isolated factor [9][10][11] and when examined in combination with ketogenic diets. 12 Neurologically impaired, nonambulatory children appear to be at particularly high risk for kidney stone development when taking topiramate, with 1 study demonstrating a 54% incidence of urolithiasis among a group of 24 such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings highlight an important association between topiramate usage and stone development and confirm the results of several previous studies. Topiramate has previously been associated with an increased risk for nephrolithiasis in patients with refractory epilepsy, both as an isolated factor [9][10][11] and when examined in combination with ketogenic diets. 12 Neurologically impaired, nonambulatory children appear to be at particularly high risk for kidney stone development when taking topiramate, with 1 study demonstrating a 54% incidence of urolithiasis among a group of 24 such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Topiramate has previously been associated with an increased risk for nephrolithiasis in patients with refractory epilepsy, both as an isolated factor [9][10][11] and when examined in combination with ketogenic diets. 12 Neurologically impaired, nonambulatory children appear to be at particularly high risk for kidney stone development when taking topiramate, with 1 study demonstrating a 54% incidence of urolithiasis among a group of 24 such patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this patient elected to continue TPM because of the quality of life seizure control provided by the medication. Other studies have also reported patient preference to continue these medications despite renal stone events due to overall quality of life considerations …”
Section: Expert Commentarymentioning
confidence: 99%
“…Other studies have also reported patient preference to continue these medications despite renal stone events due to overall quality of life considerations. 34 As the data to guide management of patients with nephrolithiasis on TPM or ZNS are limited, decisions on therapy must be individualized with shared decision making for each patient. A patient who forms a stone while on TPM or ZNS therapy should undergo a standard metabolic stone workup to establish the baseline urinary and serum parameters.…”
Section: Expert Commentarymentioning
confidence: 99%